Scales to Assess Knowledge, Motivation, and Self-Efficacy for HIV PrEP in Colombian MSM: PrEP-COL Study - Héctor F. Mueses-Marín; Beatriz Alvarado-Llano; Julián Torres-Isasiga; Pilar Camargo-Plazas; Maria C. Bolívar-Rocha; Ximena Galindo-Orrego; Jorge L. Martínez-Cajas (AIDS Research and Treatment)
Objective. We evaluated the construct validity Spanish version of knowledge, stigma, norms, and self-efficacy scales regarding PrEP in MSM. Methods. Sample of 287 MSM. Exploratory confirmatory factor analysis and item response theory were used to validate the constructs. Correlations and confidence interval-based estimation of relevance analyses were conducted to correlate the scales with willingness and intention to use PrEP. Results. Attitude, stigma, and descriptive and subjective norms scales showed good construct validity and were related to intention and willingness to use PrEP. However, the knowledge scale and self-efficacy scales require further refinement. Conclusions. The study provides useful information for assessing information, motivation, and self-efficacy related to PrEP use. Our results could be used to test the scales and the theoretical model in other contexts to confirm their usefulness.